Forgiving the enemy: a comparative analysis of the concept of forgiveness in Shari’ah and Malaysian law - Zawawi, Majdah; Hussin, Nasimah (UPM Press, 2015)
The law of qisas is a concept under Islamic law which allows the victim who has been physically hurt by an offender or the heirs of the deceased to a murder to play a role in determining the fate of the offender once he is found guilty. This includes the ability to choose whether to opt for equal punishment (qisas) or to demand monetary compensation (which is diyat), or to forgive the offender altogether. This article concentrates on the concept of forgiveness in qisas involving murder. The aim of the article is to show that contrary to popular criticism, the law of qisas is not about revenge. This is proven by the choice of forgiving the offender in total for the hurt or even life that he has taken. If compared to the current position in Malaysia, the right to forgive an offender is not given to the heirs of the decease but instead, it is given to the Yang di-Pertuan Agong or the Ruler of ALL States. This goes against the rights of the victim's heirs who not only is deprived of any compensation but also deprived of seeing justice done for the deceased. Malaysia is taken as an example of a modern country and the criminal law practised here is similar to many modern countries such as Singapore and India. Hence, this article submits that this concept of forgiveness should be revisited and re-applied to allow the victim or his heir(s) to decide the fate of the offenders instead of merely leaving it to the Rulers. This submission is arrived at after critically analysing primary sources being the injunctions in the Holy Qur'an and secondary sources that have interpreted its application. Meanwhile, the Malaysian position is examined in light of the Penal Code and the right to forgive as provided by the Malaysian Constitution.